CYTOMEGALOVIRUS RETINITIS WITH BELATACEPT IMMUNOSUPPRESSION. Issue Volume 16:Issues 2(2022) (March 2022) - Fan, Jason; Gong, Dan; Truong, Cecile; Miko, Benjamin; Horowitz, Jason; Chen, Royce W. S.
Abstract : Purpose: To report two cases of cytomegalovirus (CMV) retinitis in renal transplant patients after conversion to belatacept immunosuppression. Methods: Case report. Results: Case A was a 41-year-old African American man with no ocular history, chronic hepatitis B infection on entecavir, status-post living relative renal transplant for end-stage renal disease secondary to IgA nephropathy presented with a chief complaint of "blurry vision" in his right eye. Fundoscopic examination of the right eye revealed perivascular retinitis of the superior arcade extending temporally and a lesion nasal to the optic disk. The patient was diagnosed with CMV retinitis with macular involvement. Case B was a 52-year-old woman with an ocular history significant for bilateral vein occlusions treated with laser, and a medical history of hypertension, hyperlipidemia, and end-stage renal disease secondary to hypoplastic kidney status-post deceased donor renal transplant presented with one week of blurred vision in the right eye. Fundoscopic examination of the right eye revealed macular star configuration of exudates, as well as subretinal fibrosis temporal to the macula. Fundoscopic examination of the left eye showed Grade 4 vitreous haze and multiple areas of retinal whitening and hemorrhage, consistent with CMV retinitis infection. The patient was diagnosed with bilateral CMV retinitis, with macular involvement in the right eye. Conclusion: Renal transplant patients converted to belatacept immunosuppression may be at an increased risk for herpes virus infection, and thus herpes virus retinitis. Although the degree of risk remains uncharacterized, patients on belatacept therapy who are at the high risk of CMV infection (i.e., donor-positive/recipient-negative patients) should be counseled on the presenting signs and symptoms of CMV retinitis. In these cases, clinicians should also consider regular monitoring of serum CMV titers or continuation of antiviral prophylaxis. Abstract : Two cases of cytomegalovirus retinitis in renal transplant patients maintained on belatacept immunosuppression were described here. Several studies have suggested that patients taking belatacept may be predisposed to viral infections. To our knowledge, these are the first case reports of cytomegalovirus retinitis in this patient population.